Effect of Tiger Shrimp Shell Extract (Penaeus monodon) on Monosodium Glutamate-Induced Mice - Indah Saraswati; Desy Armalina; Fadila Risang Ayu; Ratna Damma Purnawati (Jurnal Kedokteran Diponegoro, 2023)
Background: The shell is a part of the tiger shrimp (Penaeus monodon) body that often becomes waste and has not been utilized properly, but it contains secondary antioxidants that can prevent oxidative stress in the form of astaxanthin. Although several studies have examined the function of astaxanthin as an antioxidant, the role of it in tiger shrimp shells against hepar mice induced by monosodium glutamate (MSG) is not well known